Photocatalytic and photoelectrochemical inactivation of Escherichia coli and Staphylococcus aureus - Ribeiro, Marcela Alves [UNESP]; Cruz, Jaqueline Matos [UNESP]; Montagnolli, Renato Nallin [UNESP]; Bidoia, Ederio Dino [UNESP]; Matos Lopes, Paulo Renato [UNESP] (Iwa Publishing, 2015)
Water disinfection usually requires expensive chemicals or equipment. Chlorination is a common disinfection method, although it is not able to inactivate all pathogens. High concentrations of residual chlorine also cause an unpleasant taste and smell in drinking water. As an alternative, photocatalysis and photoelectrochemical treatment has a high disinfection potential in drinking water by using solid catalysts, such as titanium dioxide. Highly reactive hydroxyl radical generated during the process serves as the main oxidant, capable of inactivating a wide range of microorganisms. In this study, we proposed a novel comparison between Gram-positive and gram-negative microorganisms. An immobilized TiO2 film promoted higher efficiency in water disinfection processes. The treatment effectively inactivated Escherichia coli and Staphylococcus aureus bacterial microorganisms in a shorter period than other alternative methods.
Keywords: Microorganisms; Semiconductor; Titanium dioxide; Water disinfection